Multiresolution Time-Frequency Analysis For Detection And Classification Of Power Quality Disturbances - Chilukuri, Venkata Mahendra (2009)
Power quality is an important issue for developed nations under deregulated power industry where the quality and reliability of power supply is utmost important in daily life. Poor quality is attributed to the various power line disturbances like voltage sag, swell, impulsive and oscillatory transients, multiple notches, momentary interruptions, harmonic and voltage flicker, etc. In order to improve the quality of electrical power it is customary to continuously record the disturbance waveforms using power-monitoring instruments. Unfortunately, most of these recorders rely on visual inspection of data record creating an unprecedented volume of data to be inspected by engineers.